Welfare and punishment: from Thatcherism to austerity - Cummins, Ian (Bristol University Press, 2021)
From Margaret Thatcher's first government to austerity politics, Ian Cummins traces changing attitudes to imprisonment and the social state. With fresh insights and critical thinking, he demonstrates how increasingly punitive approaches to crime and welfare have shaped the neoliberal economy and created stigma around those living in poverty.